Death of Public Knowledge? How Free Markets Destroy the General Intellect - Davis, Aeron (PERC, 2017)
The Death of Public Knowledge? insists upon the value of shared, publicly accessible information, and suggests that the erosion of its most visible forms, including public service broadcasting, education and the network of public libraries, will have worrying outcomes for democracy.